Combined Effects of Carbon and Nitrogen Source to Optimize Growth of Proteobacterial Methanotrophs - Tays, Catherine; Guarnieri, Michael T.; Sauvageau, Dominic; Stein, Lisa Y. (Frontiers in Microbiology, 2018)
Methane, a potent greenhouse gas, and methanol, commonly called wood alcohol, are common by-products of modern industrial processes. They can, however, be consumed as a feedstock by bacteria known as methanotrophs, which can serve as useful vectors for biotransformation and bioproduction. Successful implementation in industrial settings relies upon efficient growth and bioconversion, and the optimization of culturing conditions for these bacteria remains an ongoing effort, complicated by the wide variety of characteristics in methanotrophic isolates. Here we demonstrate the variable growth outcomes of five methanotrophic strains – Methylocystis sp. Rockwell, Methylocystis sp. WRRC1, Methylosinus trichosporium OB3b, Methylomicrobium album BG8, and Methylomonas denitrificans FJG1 – grown on either methane or methanol, at three different concentrations, with either ammonium or nitrate provided as nitrogen source. Maximum optical density, growth rate, and biomass yield were assessed for each condition. Further metabolite and FAMEs analyses were completed for Methylocystis sp. Rockwell and M. album BG8. The results indicate differential response to these growth conditions, with a general preference for ammonium-based growth over nitrate, except for M. denitrificans FJG1. Methane was also preferred by most strains, with methanol resulting in unreliable or inhibited growth in all but M. album BG8. Metabolite analysis points to monitoring of excreted formic acid as a potential indicator of adverse growth conditions, while the magnitude of FAMEs variation between conditions may point to strains with broader substrate tolerance. These findings suggest that methanotroph strains must be carefully evaluated before use in industry, both to identify optimal conditions and to ensure that strain selection is appropriate for the process of interest. This work is a step towards optimizing growth strategies for these promising microorganisms for their efficient and successful bioconversion of single-carbon substrates into value-added products.